Evaluation of the Implementation of the Tahfiz Al-Quran 30 Juz Program (Context, Inputs, Processes, and Products) at the Islamic Centre North Sumatra - Izzah, Nurul; Halimah, Siti; Haidir, Haidir (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
The Context, Input, Process, Product (CIPP) evaluation model is important because it provides a comprehensive framework for thoroughly assessing the context, inputs, processes, and products of a program. This descriptive qualitative research aims to evaluate the implementation of the tahfiz 30 juz Al-Quran program at the North Sumatra Islamic Center using the CIPP (Context, Input, Process, Product) evaluation model. Data collection was obtained through interviews, observations, and documentation. Data sources were obtained from tahfiz teachers, students, ma'had mudir, alumni, and the surrounding community and analyzed using the Miles-Huberman technique. The results of the study show that from the CIPP evaluation of the implementation of the tahfiz Al-Qur'an program at the Islamic Center of North Sumatra are: 1) Context, this program is supported by the government, schools, and the community, and is a need and part of the school's vision, mission, and goals, 2) Input, This program has competent teachers with the right teacher-student ratio (1:15) and good implementation procedures, including exam schedules, syllabus, and appropriate lesson plans, 3) The tahfiz learning process is according to plan, teachers master the material, varied methods and deposit assessment is carried out without mushaf, and 4) The product, the competence of tahfiz students is good, with the ability to read the Qur'an fluently and understand tajwid, and have noble morals that are reflected in daily behavior. It is clear that the tahfiz Al-Quran program at the North Sumatra Islamic Center runs well and effectively, is supported by various parties, has proper implementation procedures, and produces students who are competent in tahfiz and have noble character.